2011
DOI: 10.1007/s10143-011-0334-5
|View full text |Cite
|
Sign up to set email alerts
|

Chordomas of the skull base and cervical spine: clinical outcomes associated with a multimodal surgical resection combined with proton-beam radiation in 40 patients

Abstract: Previous studies of chordoma have focused on either surgery, radiotherapy, or particular tumor locations. This paper reviewed the outcomes of surgery and proton radiotherapy with various tumor locations. Between 2001 and 2008, 40 patients with chordomas of the skull base and cervical spine had surgery at our hospital. Most patients received proton therapy. Their clinical course was reviewed. Age, sex, tumor location, timing of surgery, extent of resection, and chondroid appearance were evaluated in regard to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 56 publications
3
46
3
Order By: Relevance
“…7,14,43 The physical functioning of the patients in this study was reflected by a mean KPS score of 82, which is similar to that reported in the literature for other patients with skull base chordoma (mean KPS score range 69-84). 7,14,43,60 The congruence of the study cohort clinical characteristics with published data supports the external validity of our questionnaire. Internal validity was supported using previously validated functional and quality of life outcome instruments.…”
Section: 3457supporting
confidence: 77%
“…7,14,43 The physical functioning of the patients in this study was reflected by a mean KPS score of 82, which is similar to that reported in the literature for other patients with skull base chordoma (mean KPS score range 69-84). 7,14,43,60 The congruence of the study cohort clinical characteristics with published data supports the external validity of our questionnaire. Internal validity was supported using previously validated functional and quality of life outcome instruments.…”
Section: 3457supporting
confidence: 77%
“…The estimated OS rate was 89.5% for males versus 66.7% for females (P ¼ .5). 44 Likewise, the Heidelberg group did not observe a significant OS difference in 44 patients with chordoma who received carbon ion radiation therapy. 45 Those results are in keeping with other published series.…”
Section: Sex and Survivalmentioning
confidence: 88%
“…17 Although chordoma does have a metastatic potential, its long term outcomes are mostly dependent on its local aggressiveness and pattern of local recurrence, affecting >50% of patients and requiring repeated surgical procedures and/or radiation therapy. 18 Due to their deep anatomic site, the proportion of local relapse is higher in skull base chordomas, 19 even after macroscopic complete surgery and/or definitive radiotherapy. Metastases have been reported in 30-40% of patients, with a late clinical presentation, commonly to the lungs, liver, bone, sub-cutis, lymph nodes and other sites.…”
Section: Chordomamentioning
confidence: 99%